Non‐Invasive Prenatal Testing: UK Genetic Counselors' Experiences and Perspectives. Issue 2 (15th October 2014) - Alexander, Elizabeth; Kelly, Susan; Kerzin‐Storrar, Lauren
Abstract: To date, NIPT in the UK has been predominately used in the health service for early sexing of pregnancies at known risk of sex‐linked conditions. Developments in the technology are broadening its use to diagnostic testing for paternally inherited genetic conditions and for detection of aneuploidy. This study aimed to examine the experiences of UK genetic counselors with offering NIPT for sexing, and to explore their views on future uses of the technology. Twenty interviews with practicing GC's from four centres were audiotaped, transcribed, and analyzed using modified grounded theory. Participants all had experience of counseling patients around prenatal diagnosis and 18/20 had experience of offering NIPT. GCs reported initially feeling cautious about offering the test, although they saw it as a positive advance for their patients at genetic risk. Emphasis was placed on accuracy, adequate counseling provision and gatekeeping with concerns expressed about broadening its use in the routine antenatal setting. Findings indicate the genetics model for offering prenatal testing to high risk patients can incorporate NIPT and the profession may have a role in informing its implementation in wider healthcare settings. In a wider context this study highlights the challenges new technologies bring to genetic counselors' practice and service structure.